PROYECTO DE FACTIBILIDAD PARA LA IMPLEMENTACIÓN DE UNA EMPRESA DE SERVICIOS FUNERARIOS EN LA CIUDAD DE CATACOCHA - Eras Guajala, Katy Fernanda (2016)
This research was conducted in the city Catacocha, in order to improve the economic situation of the canton. The objective guiding the development of the research is: Conduct a feasibility project for the implementation of a funeral services company in the City of Catacocha. Through this objective it is searched how to implement the business so that its feasibility is determined creation. In which each is detailed logical procedures to be followed in an investment project. Some methods that were used to meet market acceptance and acceptance of the project among them is the deductive and inductive method was used for this investigation. As we target specific market research is very important because it analyzes the market, ie demand. For all these surveys it was conducted both 343 applicants and then determining the unsatisfied demand is 114 for the first year. Marketing strategies were also analyzed, for which the four P (price, product, place and promotion) was analyzed. Another specific objective to carry out a technical study that refers to the determination of the technology used in the company, physical plant space and human resources. The place for the implementation of the company is the Catacocha City, Paltas Canton at Manuel Vivanco between Celi and José Manuel Ortiz Pacific. The amount of investment for this project is $ 95,649.48. an organizational proposal for the company, facilitates study was established to determine the business group constitution, organization and functions manuals. As another specific objective have the financial evaluation through financial indicators Finally the project evaluation was performed to establish the suitability of the project and its implementation for which the following indicators 5 such as net present value (NPV) is of $ 19,532 was analyzed 43 therefore the project is accepted; Internal Rate of Return (IRR) danto a total of 16.83%, still higher than the rest of opportunity and therefore it is profitable; Benefit Cost Ratio (RB / C) it is 0.11 cents. Capital Recovery Period (PRC) is 8 years, 8 months, 1 days; sensitivity analysis on the rise in costs is 7.02% for a total of 0.9902878 and sensitivity analysis decrease in revenues is 5.98%, indicating that the same is favorable the implementation of the project . Whose conclusions it is determined that the project is feasible therefore can be implemented and a recommendation would be to implement a company is advisable to do a good market research, because it is the starting point of the project which can undermine any risk that might exist, so that their profitability and success is guaranteed